Clinical and gasometric behavior in acute respiratory failure treated with a high-flow nasal cannula - Palencia-Mojica, Clara Lizeth; Valero-Ortiz, Adriana Sofía; Silva-Rodríguez, Laura Jimena (Universidad y Salud, 2020)
Introduction: High-flow nasal cannula offers an alternative treatment approach to conventional oxygen therapy in adults. Objective: To establish the clinical and gasometric behavior of patients with acute respiratory failure who live at 2,600 m.a.s.l. and are treated with high-flow nasal cannula in an adult intensive care unit. Materials and methods: Quasi-experimental pilot study with a pretest-posttest within-subject design and a sample size of 14 patients calculated through Epidat. A non-probabilistic convenience sampling was conducted for fourteen months. Results: 78% of the patients were women and their average age was 68 years. Chronic Obstructive Pulmonary Disease (COPD) was diagnosed in 71.42% of the cases. An oxygen flow rate of 30 L/min was administered to patients with Chronic Obstructive Pulmonary Disease, while higher rates were used for the rest of the diagnoses. Nasal cannula treatment led to (i) a decreased respiratory function, (ii) a gradually improved arterial blood pressure in patients with hypoxemic failure, (iii) and a progressively increased oxygenation rate. Conclusions: High-flow nasal cannula is a useful therapeutic option in the management of patients with acute respiratory failure living at 2,600 m.a.s.l. because it improves oxygenation and reduces respiratory function.